Evaluation of Attention-deficit/Hyperactivity Disorder in Referred Patients to the PKU Clinic in Yazd, Iran: ADHD in PKU - Ordoei , Mahtab; Fallah, Razieh; Shafii ronizi, Abolfazl (Iranian Journal of Child Neurology, 2023)
Objective Imbalance of phenylalanine (PA) to tyrosine level and decrease dopamine brain level in phenylketonuria (PKU) patients may be have a role in susceptibility of them to have attention-deficit/hyperactivity disorder (ADHD). This study was done to evaluate frequency of ADHD in referred patients to PKU Clinic in Yazd, Iran. Materials & Methods In this cross-sectional analytical study, all older than 3 years PKU patients who were referred to PKU Clinic of Shahid Sadoughi Hospital, Yazd, Iran in 2018 evaluated and ADHD symptoms in them was assessed via parent face-to-face interview. The patient had ADHD if had at least score of 20 in ADHD diagnostic rating scale via parent interview based on DSM-VI criteria. Results Fourteen boys and 21girls with mean age of 9.55±1.8 years were evaluated that 51.5% of diagnosed with PKU had ADHD. ADHD was more frequent in girls (77.8% vs. 41% in boys, P=0.03). Mean age of diagnosis of PKU was significantly higher in patients with ADHD (52.54±15.65 months vs. 29.75±9.65 months, P = 0.03). Mean of PA level in the last 6 months (15.59±5.95 vs. 8.72+5.18, P= 0.005) and mean of the last six PA level (14.76±4.71 vs. 8.96±3.86, P= 0.03) were significantly higher in ADHD group. Conclusion Prevalence of ADHD in phenylketonuria patients in present study was much more than other studies. Late diagnosis of PKU and long term high phenylalanine blood and brain level might be associated with its increased and neonatal screening, regular follow-up and continuous evaluation of PKU patients for ADHD symptoms should be performed.